Odontogenic Pain and Its Associated Factors in Children of Peshawar, Pakistan - Mashooq Khan, Noor-Ud-Din, Jawad Tariq, Rafia Awais Qazi, Aqsa Mumtaz, Abid Rahim (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To determine odontogenic pain and its associated risk factors in children’s presenting to a Pediatric Dentistry Department Khyber College of Dentistry Peshawar. Material and method: This cross-sectional study was conducted at the pediatric department of Khyber College of Dentistry Peshawar. A convenience method was adopted for sampling and data was collected through a pre-design structured Proforma filled in the outpatient department (OPD) of the pediatric dentistry department. Data were analyzed by using a statistical package for social science SPSS. Frequencies and percentages were obtained. Results: Overall three hundred and ninety-five (395) children were engaged in this study. In which 60% were male and 40% female. All the participants attributed some signs and symptoms of odontogenic pain enlisted in Proforma. Dental caries with 71% was the most common associated factor which caused odontogenic pain. Periodontitis was 4%. Dental trauma was 19%. Dental hypersensitivity was 1% and other factors like eruption pressure and para functional habits etc. were 4%. Conclusion: It is concluded from this study that all of the patients attending the pediatric dentistry department of Khyber College of Dentistry Peshawar were having odontogenic pain. Occurring mainly in the teeth that present dental caries. Most patients were male and a higher frequency of the pain was evident in the patient’s age group ranging from 8-12 years i.e., in a mixed dentition period. The second peak frequency ‘of odontogenic pain was due to dental trauma. A total of five cases were reported, in which the cause of odontogenic pain was dental hypersensitivity which was the lowest percentage. Keywords: Odontogenic Pain, Dental Caries, Trauma, Hypersensitivity, and Periodontitis,